Private Saving Accelerations - Ebeke, Christian (IMF Working Papers; Working Paper ;, 2014)
Domestic private saving rates have been on a declining trend in many Emerging Markets (EMs), raising questions about countries' ability to generate sufficient domestic resources to finance investment. This paper examines how countries have managed to achieve protracted increases in the private saving rate. The results show that episodes of sustained accelerations of private savings are mostly the result of very strong macroeconomic performance. Econometric investigations using matching estimators do not reject the result that stronger economic growth mostly precedes episodes of saving accelerations.